On the Dual Role of Carcinoembryonic Antigen-Related Cell Adhesion Molecule 1 (CEACAM1) in Human Malignancies. (14th October 2018) - Calinescu, Andreea; Turcu, Gabriela; Nedelcu, Roxana I.; Brinzea, Alice; Hodorogea, Anastasia; Antohe, Mihaela; Diaconu, Carmen; Bleotu, Coralia; Pirici, Daniel; Jilaveanu, Lucia B.; Ion, Daniela A.; Badarau, Ioana A.
Abstract : Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is a glycoprotein belonging to the carcinoembryonic antigen (CEA) family that is expressed on a wide variety of cells and holds a complex role in inflammation through its alternate splicing and generation of various isoforms, mediating intricate mechanisms of modulation and dysregulation. Initially regarded as a tumor suppressor as its expression shows considerable downregulation within the epithelia in the early phases of many solid cancers, CEACAM1 has been linked lately to the progression of malignancy and metastatic spread as various papers point to its role in tumor progression, angiogenesis, and invasion. We reviewed the literature and discussed the various expression patterns of CEACAM1 in different types of tumors, describing its structure and general biologic functions and emphasizing the most significant findings that link this molecule to poor prognosis. The importance of understanding the role of CEACAM1 in cell transformation stands not only in this adhesion molecule's value as a prognostic factor but also in its promising premise as a potential new molecular target that could be exploited as a specific cancer therapy.